Primary breast angiosarcoma in postmenopausal woman: case study and the literature review - Jońska-Gmyrek, Joanna; Bakuła-Zalewska, Elwira; Gałecki, Jacek; Żółciak-Siwińska, Agnieszka; Gmyrek, Leszek (Menopause Review/Przegląd Menopauzalny, 2013)
A case of an 83-year-old female patient, who was admitted to the Centre of Oncology in Warsaw because of the right breast tumor, is presented. There was no exposure to prior irradiation. In two biopsies of the lesion, its malignant nature was not confirmed. Breast tumor removal with wide surgical margins was performed. As a result of the examination, angiosarcoma was confirmed histologically. Given the result, a simple right breast amputation was performed. External beam radiotherapy and chemotherapy, due to the rapid local recurrence and distant metastases, were also performed. The patient died after 20 months of the initial diagnosis because of the disease progression.